Post-operative neutrophil-to-lymphocyte ratio and outcome after thrombectomy in acute ischemic stroke - Li, Shen-Jie; Cao, Shan-Shan; Huang, Pei-Sheng; Nie, Xin; Fu, Yang; Liu, Jian-Ren (Frontiers in Neurology, 2022)
Background Neutrophil to lymphocyte ratio (NLR) is a novel inflammatory marker to predict adverse cardiovascular events. However, there is a lack of data on hemorrhagic transformation (HT) and neurological outcome after mechanical thrombectomy in acute ischemic stroke (AIS). We investigated whether NLR before and after thrombectomy for patients with AIS was associated with HT and neurological outcomes. Methods We performed a retrospective analysis of consecutive patients with anterior circulation AIS who underwent thrombectomy. HT was evaluated by CT within 24 h after thrombectomy. Clinical data had been collected retrospectively; laboratory data were extracted from our electronic hospital information system. NLR was obtained at admission (NLR1) and immediately after thrombectomy (NLR2). The main outcomes were post-interventional intracranial hemorrhage and unfavorable functional status (modified Rankin scale scores of 3–6) 3 months post-stroke. Results A total of 258 patients with AIS, according to the NIHSS (median 14), were included. NLR2 was higher in patients who developed HT after thrombectomy and unfavorable neurological outcomes 3 months post-stroke (p < 0.001) than in those without HT or favorable outcomes, even after correction for co-factors [Odds Ratio (OR) 1.35 for HT, 95% confidence interval (CI)1.16–1.57, p < 0.001, and 1.85 for unfavorable outcome, 95%CI 1.57–2.17, p < 0.001]. The optimal cutoff value for the NLR2 as an indicator for auxiliary diagnosis of HT and the unfavorable outcome was 8.4 and 8.8, respectively. Conclusion NLR immediately after thrombectomy is a readily available biomarker of HT and neurological outcomes in patients with AIS.